An Assessment of the Status of Women in Ventura County, 2011: A report compiled by CSU Channel Islands Sociology students as a service-learning capstone project - de Paula, Mia; Fuller, Celene; Rincon, Marisol; Kajaty, Bernadette; Downey, Dennis (CBR@CSUCI: An annual volume of community-based research, 2019)
This report was completed as a service-learning project by Sociology capstone students at California State University, Channel Islands, in collaboration with the Ventura County Commission for Women (VCCW). The report is a compilation of publically available secondary data designed to assist the VCCW in evaluating the general status and particular needs of women in the county. Throughout the report, comparisons are made between women and men, or between Ventura County and larger geographic aggregations (California and the United States as a whole). Findings are presented in the following areas: demographics; educational attainment; employment and earnings; household composition and homelessness; political participation; health and well-being; child care and Women, Infants, and Children assistance; and violence and safety.